Leptin into the rostral ventral lateral medulla (RVLM) augments renal sympathetic nerve activity and blood pressure - Barnes, Maria J.; McDougal, David H. (Frontiers in Neuroscience, 2014)
Leptin is a hormone released from adipose tissue. While this hormone normally acts to reduce feeding behavior and increase energy expenditure, in obesity, resistance to these effects occurs even though the hormone is released in large amounts. Although leptin no longer works to suppress feeding in the obese, leptin retains its potent effects on other autonomic functions such as blood pressure regulation. Leptin has been associated with hypertension and increased sympathetic autonomic activity. Therefore, leptin is emerging as a major contributor to the hypertensive state observed in obesity. Sympathetic control of blood pressure is maintained principally by autonomic reflex control circuits in the caudal brainstem. The rostral ventral-lateral medulla (RVLM) is the primary regulator of the sympathetic nervous system, sending excitatory fibers to sympathetic preganglionic neurons to regulate sympathetic control over resistance vessels and blood pressure. Previous studies from our laboratory have shown that neurons in the ventral lateral medulla express leptin receptors (ObRb). Our present study using pseudo-rabies multi-synaptic retrograde tract tracing and immunohistochemical methods revealed that neurons within the RVLM that send sympathetic projections to the kidney express leptin receptors. Acute microinjection of leptin (1 and 3 μg; 40 nL) into the RVLM evoked a significant increase in Mean Arterial Pressure (MAP) and renal sympathetic nerve activity (RSNA). When the 3 μg dose of leptin was preceded with a leptin antagonist, (SLAN-4; 1 ng), it attenuated the cardiovascular response of leptin. Taken together, these data suggest that leptin's actions within the RVLM may influence blood pressure and renal sympathetic nerve activity.